Production of 4-Deoxy-L-erythro-5-Hexoseulose Uronic Acid Using Two Free and Immobilized Alginate Lyases from Falsirhodobacter sp. Alg1 - Yuzuki Tanaka; Yoshihiro Murase; Toshiyuki Shibata; Reiji Tanaka; Tetsushi Mori; Hideo Miyake (Molecules, 2022)
Falsirhodobacter sp. alg1 expresses two alginate lyases, AlyFRA and AlyFRB, to produce the linear monosaccharide 4-deoxy-L-erythro-5-hexoseulose uronic acid (DEH) from alginate, metabolizing it to pyruvate. In this study, we prepared recombinant AlyFRA and AlyFRB and their immobilized enzymes and investigated DEH production. Purified AlyFRA and AlyFRB reacted with sodium alginate and yielded approximately 96.8% DEH. Immobilized AlyFRA and AlyFRB were prepared using each crude enzyme solution and κ-carrageenan, and immobilized enzyme reuse in batch reactions and DEH yield were examined. Thus, DEH was produced in a relatively high yield of 79.6%, even after the immobilized enzyme was reused seven times. This method can produce DEH efficiently and at a low cost and can be used to mass produce the next generation of biofuels using brown algae.